Timing Matters: HIV Testing Rates in the Emergency Department - Rebecca Schnall; Nan Liu (Nursing Research and Practice)
Study Objectives. In response to the 2010 New York State HIV testing law, we sought to understand the contextual factors that influence HIV testing rates in the emergency department (ED). Methods. We analyzed electronic health record logs from 97,655 patients seen in three EDs in New York City. We used logistic regression to assess whether time of day, day of the week, and season significantly affected HIV testing rates. Results. During our study period, 97,655 patients were evaluated and offered an HIV test. Of these, 7,763 (7.9%) agreed to be tested. Patients arriving between 6 a.m. and 7:59 p.m. were significantly (P<0.001) more likely to be tested for HIV, followed by patients arriving between 8:00 p.m. and 9:59 p.m. (P<0.01) and followed by patients arriving between 5–5:59 a.m. and 10–10:59 p.m. (P<0.05) compared to patients arriving at midnight. Seasonal variation was also observed, where patients seen in July, August, and September (P<0.001) were more likely to agree to be tested for HIV compared to patients seen in January, while patients seen in April and May (P<0.001) were less likely to agree to be tested for HIV. Conclusion. Time of day and season affect HIV testing rates in the ED, along with other factors such as patient acuity and completion of other blood work during the ED visit. These findings provide useful information for improving the implementation of an HIV testing program in the ED.